2010
DOI: 10.1093/aob/mcq027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiology of elemental distributions in plants

Abstract: Element accumulation patterns are clearly defined by expression of key ion or solute transporters. Although the location of element accumulation is fairly robust, alterations in expression of certain solute transporters, through genetic modifications or by growth under stress, result in perturbations to these patterns. However, redundancy or induced pleiotropic expression effects may complicate attempts to characterize the pathways that lead to cell-specific elemental distribution. Accumulation of one element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
262
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(277 citation statements)
references
References 283 publications
12
262
3
Order By: Relevance
“…The -P microanalysis values are related to the low total concentration of that nutrient in needles (Table 2). Unlike the present study where there was no variation among the specialized tissues, Conn and Gilliham (2010) reported that monocots accumulate P in the mesophyll, while dicots accumulate P in the epidermis. In addition, -P was the only treatment in which this element was not detected in the spongy mesophyll and abaxial epidermis (Figure 2a).…”
Section: Elemental Distribution In Epidemis and Mesophyllcontrasting
confidence: 99%
See 1 more Smart Citation
“…The -P microanalysis values are related to the low total concentration of that nutrient in needles (Table 2). Unlike the present study where there was no variation among the specialized tissues, Conn and Gilliham (2010) reported that monocots accumulate P in the mesophyll, while dicots accumulate P in the epidermis. In addition, -P was the only treatment in which this element was not detected in the spongy mesophyll and abaxial epidermis (Figure 2a).…”
Section: Elemental Distribution In Epidemis and Mesophyllcontrasting
confidence: 99%
“…These results indicate that in palisade mesophyll there is a greater accumulation of organic molecules containing S. Likewise, Mastroberti and Mariath (2003) reported an accumulation of phenolic compounds and a large number of chloroplasts in A. angustifolia; both generally contain S in their composition. Conn and Gilliham (2010) also reported higher S concentrations in the mesophyll compared to the epidermis of monocot and dicot leaves.…”
Section: Elemental Distribution In Epidemis and Mesophyllmentioning
confidence: 86%
“…8,10,19,23,33 Higher Cd accumulation in roots than leaves suggest that Cd transport to the xylem is restricted, therefore less in above ground parts, suggesting that Cd is not readily translocated in the phloem. 6,34,35 Furthermore, Cd accumulation in the root and leaf also depends on binding to the extracellular matrix. 36 It has also been reported that Cd accumulation by plants grown in soil is directly related to transpiration and thereby to stomatal conductance.…”
Section: Introductionmentioning
confidence: 99%
“…1 For instance, it is generally observed that phosphate and calcium (Ca) do not co-localize to high concentrations in the same cell vacuole; if they did it would be expected that a large proportion of both elements would exist as insoluble calcium phosphate. 1 In contrast, magnesium (Mg), potassium (K), chloride and nitrate may share similar cellular locations but can be at very different concentrations in different cells. 1,2 Furthermore, the cellular location of a particular element is robust within an individual plant, but the cell-type that accumulates each element can vary between species.…”
Section: Introductionmentioning
confidence: 99%